The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1002/polb.23316
|View full text |Cite
|
Sign up to set email alerts
|

Influence of multiple stimuli on the lower critical solution temperature of new cationic poly(N‐acryloyl‐N′‐ethylpiperazine‐co‐N‐isopropylacrylamide) solutions

Abstract: New multi-stimuli responsive cationic copolymers based on N-acryloyl-N 0 -ethyl piperazine (AcrNEP) and N-isopropylacrylamide (NIPAM) were prepared by thermal free-radical solution polymerization in dioxane at 75 C. The chemical composition of the copolymers was determined by 1 H NMR spectroscopy and was found that the copolymers were slightly rich in NIPAM content than that of AcrNEP. The reactivity of the two monomers for the copolymerization reaction was evaluated by the extended Kelen-T€ ud€ os method. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 74 publications
0
3
0
Order By: Relevance
“…Previous reports have shown that some salts or metal ions, the chaotropic agent, increase LCST (“salting‐in” effect), whereas others salts, the kosmotropic ones, decrease LCST (“salting‐out” effect) . The thermosensitivity of the copolymer is derived from the hydrophilic/hydrophobic interaction related to the copolymer chains and water molecules .…”
Section: Resultsmentioning
confidence: 99%
“…Previous reports have shown that some salts or metal ions, the chaotropic agent, increase LCST (“salting‐in” effect), whereas others salts, the kosmotropic ones, decrease LCST (“salting‐out” effect) . The thermosensitivity of the copolymer is derived from the hydrophilic/hydrophobic interaction related to the copolymer chains and water molecules .…”
Section: Resultsmentioning
confidence: 99%
“…Secondly, it becomes obvious that T ass is shifted towards the lower temperature with increasing NaCl concentration and this trend originates from the salting-out effect of NaCl on the grafted side chains, which has been widely reported for other LCST polymers (30)(31)(32)(33)(34). As a matter of fact, the addition of NaCl reduces the quality of the solvent for the grafted side chains and consequently the hydrophobic association occurs at a lower temperature compared to pure water (17).…”
Section: Effect Of Salt Concentrationmentioning
confidence: 93%
“…The rapid coil-to-globule transition of PNIPAM chain in aqueous solution gives rise to the lower critical solution temperature (LCST) at around 32 C. 58 The main mechanism of the aqueous phase separation of PNIPAM is the thermally induced release of water molecules bound to the polymer isopropyl side groups, which results in increasing intra-and intermolecular hydrophobic interactions between the isopropyl groups above its LCST. The LCST can also be easily adjusted by copolymerizing of NIPAM with other functional segments through the control of di®erent hydrophilic/hydrophobic balance.…”
Section: Poly(n-isopropylacrylamide) (Pnipam)mentioning
confidence: 99%